Pattern of neurological recovery in persons with an acute cervical spinal cord injury over the first 14 days post injury - Fallah, Nader; Noonan, Vanessa K.; Waheed, Zeina; Charest-Morin, Raphaele; Dandurand, Charlotte; Cheng, Christiana; Ailon, Tamir; Dea, Nicolas; Paquette, Scott; Street, John T.; Fisher, Charles; Dvorak, Marcel F.; et al. (Frontiers in Neurology, 2023)
Introduction: Following a traumatic spinal cord injury (SCI) it is critical to document the level and severity of injury. Neurological recovery occurs dynamically after injury and a baseline neurological exam offers a snapshot of the patient's impairment at that time. Understanding when this exam occurs in the recovery process is crucial for discussing prognosis and acute clinical trial enrollment. The objectives of this study were to: 1) describe the trajectory of motor recovery in persons with acute cervical SCI in the first 14 days post-injury; and 2) evaluate if the timing of the baseline neurological assessment in the first 14 days impacts the amount of motor recovery observed. Methods: Data were obtained from the Rick Hansen Spinal Cord Injury Registry (RHSCIR) site in Vancouver and additional neurological data was extracted from medical charts. Participants with a cervical injury (C1-T1) who had a minimum of three exams (including a baseline and discharge exam) were included. Data on the upper-extremity motor score (UEMS), total motor score (TMS) and American Spinal Injury Association Impairment Scale (AIS) were included. A linear mixed-effect model with additional variables (AIS, level of injury, UEMS, time, time2, and TMS) was used to explore the pattern and amount of motor recovery over time. Results: Trajectories of motor recovery in the first 14 days post-injury showed significant improvements in both TMS and UEMS for participants with AIS B, C, and D injuries, but was not different for high (C1-4) versus low (C5-T1) cervical injuries or AIS injuries. The timing of the baseline neurological examination significantly impacted the amount of motor recovery in participants with AIS B, C, and D injuries. Discussion: Timing of baseline neurological exams was significantly associated with the amount of motor recovery in AIS B, C, and D injury. Studies examining changes in neurological function should consider stratifying by severity and timing of the baseline exam to reduce bias amongst study cohorts. Future studies should validate these estimates for AIS B, C and D injuries to see if they can serve as an ‘adjustment factor’ to control for differences in the timing of the baseline neurological exam.